What do we know about long-term effects of disasters on mental health? - Ajduković, Dean (Array, 2014)
The systematic literature review and meta-analysis of long-term psychological effects of disasters was performed on primary studies of journal articles, chapters, dissertations, conference papers and unpublished reports produced between 1980 and 2013. Literature search included databases PsycINFO, SocINDEX, Cinahl, Medline, Web of Science, Scopus, Academic Search Complete, and PILOTS with 1, 036 documents identified. Disasters were defined as single, sudden, with clear beginning and ending, resulting in major disruption of community functions, natural or human-made, requiring mobilization of major efforts. Wars and armed conflicts except terrorism were excluded. Long-term was any period longer than 6 months. The eligible studies used either cross-sectional or prospective research designs. The number of studies enabled meta-analysis of four psychological outcomes in the affected groups: General mental health was poorer at 12 months and 6.6 years post-disaster ; post-traumatic stress symptoms remained higher at 8.4 years ; 3 years post-disaster odds for prevalence of PTSD diagnoses were 9:1 ; depression symptoms were moderately and significantly higher only beyond 18 months indicating a possible delayed depression response ; 11 years post-disaster odds for depression diagnoses were 5:1. Individuals affected by disasters have worse long-term mental health outcomes compared to the non-affected or to the pre-disaster period. The major gap of lack of research at the community and societal level was identified.